Soil fertility mapping, land suitability assessment for suggesting maize and pomegranate crops in Hosakere micro-watershed of Davanagere district, Karnataka - GOWDA, J. VENKATE; ANILKUMAR, S. N.; SATHISH, A.; RAMAKRISHNA PARAMA, V. R. (Journal of Soil and Water Conservation, 2018)
A study was conducted to evaluate the status of major, secondary and micronutrients as affected by different physiographic units and land suitability for agriculture and horticulture crops in Hosakere micro-watershed (632 ha) of Davanagere district during 2015. Ninety nine samples were collected at 250 m grid spacing within the micro-watershed representing all the physiographic positions in landscape and major crops grown. The fertility maps were prepared for the area using Arc GIS 10.4 and spatial analyst using exponential function for kriging (geostatical wizard). Maize and pomegranate being major crops in this area, the larger area of the micro watershed (414 ha) is covered by gravelly (35-60% gravel) soils, it becomes major constraint for suitability followed by shallow depth of soil (25-50 cm) and deficiency of nitrogen, phosphorus and zinc (83.2%, 60.91% and 70.19% of area, respectively) leading to poor productivity of these crops. Land suitability criteria indicates maize and pomegranate are less suitable due to gravelliness and shallow depth. Hence, alternate crop like finger millet is recommended in such type of lands. Further, the areas which are low in nutrient status (N, P and Zn) needs to be improved by applying sufficient FYM, compost and fertilizers such as urea, SSP, DAP, rock phosphate and ZnSO4 for achieving higher yields.